Online database usage among administration science students / Nur Adibah Harun - Harun, Nur Adibah (2012)
The present study to intend the usage of online database which is covered by the pattern of usage and the awareness of online database. This study had been done in Perpustakaan Sultan Badlishah at UiTM Kedah. Close ended questionnaires was distribute to the respondents which is Administration Science Student in UiTM Kedah. Online database were fully use by Administration Science Student which is majority of them were agree that they used the online database used for searching new information, reading full-text articles, reading abstracts, and browsing the table of contents. There are variety of pattern of usage of online database which is some of them were used the search strategy like searching information by topic, subject, tables of contents, indexes, Boolean searching and more. Majority of the respondents were aware of the existences and the advantages of online database and only a few respondents were not aware. The library should conduct a workshop or seminar on how to search information through library online database as well as into expose the student with the Boolean strategy searching for the student, especially the first intake students. In conclusion, it was identifying that nearly 50 per cent of the respondents was agree and fully use of online database into find the information.